A framework to analyse the effect of hotel websites stimuli on emotions, attitude and intentions moderated by sensory curiosity; language of instruction; classification of hotel; and annual income of customer - Sarkar, B.; Loureiro, S. M. C. (PROCEEDINGS TMS ALGARVE 2012: Tourism Management, Marketing, & ICT Management, 2013)
The present study reviews the literature about the S–O–R framework and proposes an extending model regarding attitude and behavioral intentions as responses. Additionally, the model hypothesizes that sensory curiosity, language of instruction, classification of Hotel, and annual income of customer moderate the relationships between atmospheric cues and consumers’ emotional reactions. The proposed model should be tested using two samples. One sample should gather consumers who have experience of using and booking in hotel websites. Another sample, a group of control, should be composed of people with no experience in using the hotel website for booking.